Determination of the Time and Coordinates Required for Measuring the Milky Way’s Rotation Curve Using BURT in 2023 - Mahdi, Hareth S. (Iraqi Journal of Science, 2023)
Baghdad University Radio Telescope (BURT) is a 3 meter radio telescope that was installed in the main campus of the University of Baghdad in Jadiriyah. Radio telescopes, in general, offer a wide range of applications in radio astronomy, which are usually used to detect the neutral hydrogen emission line at a wavelength of 21 cm. One of the key applications of BURT is to observe the Milky Way galaxy and to determine its rotation curve. However, performing such observations requires accurate determination of the appropriate observing time as well as the coordinates. This paper focuses on how the observing time and coordinates are calculated correctly and accurately. The horizontal coordinate that corresponds to the galactic coordinates (b=0° and 0° ≤ l ≤ 90°) in every single day of 2023 at 10 am have been calculated using a c++ code that has been written for the purpose of this work. The results showed that the appropriate time for observing the Milky Way using BURT in 2023 is during January, February, March, November and December of 2023. The medians of altitude during those months are 50.9798°, 62.7919°, 50.6198°, 9.6562° and 30.5041°, respectively. During those months, the altitude is found, in general, larger than zero which means that the galactic position is above the horizon.